2016
DOI: 10.1111/nhs.12300
|View full text |Cite
|
Sign up to set email alerts
|

Piloting staff education in Australia to reduce falls in older hospital patients experiencing delirium

Abstract: This study piloted a hospital-based delirium and falls education program to investigate the impacts on staff knowledge and practice plus patient falls. On a medical ward, staff knowledge was compared before and after education sessions. Other data -collected a day before and after program implementation -addressed documentation of patients' delirium and evidence of compliance with falls risk minimization protocols. These data, and numbers of patient falls, were compared before and after program implementation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 24 publications
2
28
0
2
Order By: Relevance
“…1 Flow chart of included studies). [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Out of the 16 papers included, eight were about delirium training, six focused on dementia care training and a further two on training to improve care of confused older patients generally (delirium and dementia). Summaries of the included studies can be found in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Flow chart of included studies). [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Out of the 16 papers included, eight were about delirium training, six focused on dementia care training and a further two on training to improve care of confused older patients generally (delirium and dementia). Summaries of the included studies can be found in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Masking was absent in all but two studies, 17,20 meaning performance bias was likely in the other six studies. 15,16,18,19,21,22 In addition, only one of the studies reported using a power calculation. 17…”
Section: Study Qualitymentioning
confidence: 99%
“…(6) Several factors may contribute to fall occurrence, such as impairments to balance, walking pace, visual acuity and cognition, as well as chronic diseases, postural hypotension, use of psychotropic medication, slippery surfaces, path obstacles and poor lighting. (3,4,7,8) Such factors may vary according to the location and the profile of care public. Therefore, identification of risk factors is important for efficient planning and implementation of fall prevention interventions, (3,4) guided by the identification of individuals with higher fall susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…As such, many researchers are exploring multifaceted education programs that address these multiple components (Gordon et al, 2013;Hickens et al, 2017;Page et al, 2010;Travers et al, 2018). Some of the challenges to implement such programs are associated with releasing staff (Bezzant, 2008), time constraints (Jones et al, 2015;Toye et al, 2017), and lack of perceived significance (Meyer at al. 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For example, on-line programs appeared to have good uptake (Detoyer et al, 2016;McCrow, Sullivan & Beattie, 2014;van de Steeg et al, 2014) and are recommended to address knowledge deficits (Irwing et al, 2009). In addition to on-line delivery, many of the available education programs include information provided in didactic lecture form (Devlin et al, 2008;Gesin et al, 2012;Gordon et al, 2013;Hickin et al, 2017;Meako et al, 2011;Page et al, 2010;Ramaswamy et al, 2010;Tabet et al, 2005;Toye et al, 2017;Wand et al, 2014).…”
Section: Introductionmentioning
confidence: 99%